Counter-Stereotypes and Feminism Promote Leadership Aspirations in Highly Identified Women - Leicht, Carola; Gocłowska, Małgorzata A.; Van Breen, Jolien A.; de Lemus, Soledad; Randsley de Moura, Georgina (Frontiers in Psychology, 2017)
Although high women identifiers are more susceptible to stereotype threat effects, women’s identification might associate with greater leadership aspirations contingent on (1) counter-stereotype salience and (2) feminist identification. When gender counter-stereotypes are salient, women’s identification should associate with greater leadership aspiration regardless of feminism, while when gender stereotypes are salient, women’s identification would predict greater leadership aspirations contingent on a high level of feminist identification. In our study US-based women (N=208) attended to gender stereotypic (vs. counter-stereotypic) content. We measured identification with women and identification with feminism, and, following the manipulation, leadership aspirations in an imagined work scenario. The interaction between identification with women, identification with feminism, and attention to stereotypes (vs. counter-stereotypes) significantly predicted leadership aspirations. In the counter-stereotypic condition women’s identification associated with greater leadership aspirations regardless of feminist identification. In the stereotypic condition women’s identification predicted leadership aspirations only at high levels of feminist identification. We conclude that salient counter-stereotypes and a strong identification with feminism may help high women identifiers increase their leadership aspirations.